2009
DOI: 10.1071/cp09172
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for drought tolerance among Australian green couch grasses (Cynodon spp.)

Abstract: Increasing demand for scarce water resources in Australia has led to the selection of turfgrass genotypes with good drought tolerance. Here we describe the development of methodologies for screening green couch grasses (Cynodon spp.) grown in 40-cm PVC pots placed under rainout shelters. The drought tolerance of up to 8 genotypes including 4 commercial varieties (CT2, Grand Prix, Legend, and Winter Green) and 4 wild Australian ecotypes (1-1, 25-a-1, 40-1, and 81-1) was examined in 3 experiments conducted in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, since leaf death is one means by which plants can conserve water in order to extend meristem life ( Munné-Bosch and Alegre, 2004 ), the leaf death score might represent survival via dehydration avoidance and not necessarily tolerance (e.g. Zhou et al , 2009 ).…”
Section: Phenotyping For Dehydration Survivalmentioning
confidence: 99%
“…However, since leaf death is one means by which plants can conserve water in order to extend meristem life ( Munné-Bosch and Alegre, 2004 ), the leaf death score might represent survival via dehydration avoidance and not necessarily tolerance (e.g. Zhou et al , 2009 ).…”
Section: Phenotyping For Dehydration Survivalmentioning
confidence: 99%
“…A study conducted using commercially available cultivars of cool-season turfgrass demonstrated that grasses having lower ET rates during drought-stress conditions resulted in greener turf (Zhao et al, 1994). Similarly, a lysimeter study of eight bermudagrass genotypes showed that those with lower ET rates remained green for longer periods after a drought treatment (Zhou et al, 2009). It also showed that the genotypes having lower ET rates had more available soil water at later stages of the drought treatment.…”
mentioning
confidence: 99%
“…Compared to the source germplasm (the germplasm present in the entire source population), the AC contains increased gene diversity (H = 0.18 versus H = 0.14), > 95% of the total number of alleles, and similar proportions of accessions representing specific climates, ploidy levels, and environment type. DNA extraction procedures and EST-SSR analyses have been reported previously (Jewell et al 2010;Kearns et al 2009;Zhou et al 2009). DNA from 59 international accessions representing global distribution was provided by the USDA-ARS in Tifton, GA (international collection; IC; Anderson et al 2009).…”
Section: Plant Materials Est-ssr Genotyping and Core Collection Devementioning
confidence: 99%
“…comprise perennial, widely adapted, warm-season grasses that serve multiple purposes in all continents of the world and are reported to have excellent heat and drought tolerance (Taliaferro 2003;Zhou et al 2009). Enormous morphological variability exists within the genus (Harlan and de Wet 1969;.…”
Section: Introductionmentioning
confidence: 99%